Aggregation‐Induced Emission: Crystallization‐Induced Emissive Invisible Ink (Advanced Optical Materials 11/2019). Issue 11 (4th June 2019) - Zerby, Nicholas; Malka, Orit; Bhattacharya, Sagarika; Nandha Kadamannil, Nila; Baranov, Mark; Jelinek, Raz
Abstract : Crystallization induced emission (CIE) of a small molecule displaying a single phenyl ring is reported by Raz Jelinek and co‐workers in article number1900232 . The fluorescence emission is ascribed to the crystalline organization of the molecule, blocking π – π stacking and concomitant non‐radiative energy dissipation. The CIE phenomenon was exploited for utilizing the molecule as an "invisible ink" on a variety of surfaces.